2007
DOI: 10.1097/mbp.0b013e32809efa51
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of dipping/nondipping pattern in untreated essential hypertensive patients: impact of sex and age

Abstract: These findings indicate that nocturnal blood pressure patterns have a limited short-term reproducibility in the whole study population as well as in different age and sex subgroups. As variability of nocturnal blood pressure patterns is not predicted by easy available clinical data, such as sex and age, a reliable classification of patients according to circadian blood pressure patterns should be obtained by repeating ambulatory blood pressure monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Therefore, these previous reports are inconclusive, and our report is the first to describe the relationship between the dipping pattern (evaluated by out-of-hospital ABPM) and cardiovascular prognosis in patients with T2DM; we found that the event rate of nondippers was not different from that of dippers. The classification of nondipping is recognized as being generally not very reproducible, 11 but this may not be the case in diabetes patients. 30 The riser (or reverse) pattern has been reported in patients with severe autonomic dysfunction, and is closely associated with adverse CV events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these previous reports are inconclusive, and our report is the first to describe the relationship between the dipping pattern (evaluated by out-of-hospital ABPM) and cardiovascular prognosis in patients with T2DM; we found that the event rate of nondippers was not different from that of dippers. The classification of nondipping is recognized as being generally not very reproducible, 11 but this may not be the case in diabetes patients. 30 The riser (or reverse) pattern has been reported in patients with severe autonomic dysfunction, and is closely associated with adverse CV events.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported that the values were reproducible in only 65.9% of "nondippers" when ABP monitoring (ABPM) was repeated without any intervention. 11 Again, most of the subjects in these studies were not diabetes patients. [5][6][7][8][9] ABPM has been widely advocated by organizations such as the American Society of Hypertension 12 and the International Society of Hypertension 13 for improving the estimation of cardiovascular risk in patients with hypertension, but the American Diabetes Association has made no recommendations on the use of out-of-office monitoring, on the grounds that there are insufficient published data in patients with diabetes.…”
mentioning
confidence: 98%
“…Keeping in mind that the reproducibility might depend on the duration and treatment of essential hypertension [30], a conversion rate between 12 and 24% (short-term variability) was reported. Thus, dipping pattern was judged to be ''highly reproducible'', but even more stable in dippers than in non-dippers [31,32]. It seems to be quite unlikely that the conversion of dipping status, as seen in half of our study population, might be only an accidental finding due to the measurement variability.…”
Section: Discussionmentioning
confidence: 82%
“…31,32 Given the limited reliability of the nondipping classification in our study, it is likely that some of the correlations have been underestimated.…”
mentioning
confidence: 84%